Market Discipline and Conflicts of Interest Between Banks and Pension Funds - Barajas, Adolfo; Catalan, Mario (Washington, D.C. : International Monetary Fund, 2011)
We study the behavior of private pension funds as large depositors in a banking system. Using panel data analysis, we examine whether, and if so how, pension funds influence market discipline in Argentina in the period 1998-2001. We find evidence that pension funds exert market discipline and this discipline gets stronger as the share of pension fund deposits in a bank rises. However, conflicts of interest undermine the disciplining role of pension funds. Specifically, pension funds allocate deposits to banks with weak fundamentals that own pension fund management companies. We conclude that forbidding banks' ownership of companies involved in pension fund management can enhance market discipline.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet